Performance of Cement Sand Brick Containing Bamboo Ash as Cement Replacement Material - S.H. Adnan, S.H. Adnan; S.N.S.M. Satti, S.N.S.M. Satti; M.A. Safea’ai, M.A. Safea’ai; M. Hairi Osman, M. Hairi Osman; W.J. Wan Amizah, W.J. Wan Amizah; Z. Jamellodin, Z. Jamellodin; P.S.E. Ang, P.S.E. Ang; W.I. Wan Mastura, W.I. Wan Mastura; J. Garus, J. Garus (2023)
Bamboo Ash is a safer and more sustainable building material. It is possible to use bamboo ash as a partial cement replacement as an alternative to cement application and also to reduce pollution. For this study, the main purpose is to determine the compressive strength and water absorption of cement sand brick containing bamboo ash. Laboratory tests such as compression tests and water absorption tests on cement sand brick with bamboo ash as a partial replacement for cement have been conducted. The mixes with various ratios using bamboo ash are 5%, 7%, and 10%. The specimen size for cement sand brick is 215 mm long, 102.5 mm wide, and 65 mm deep according to BS3921:1985. The results from the specimens containing Bamboo Ash have been compared to the control specimens. The water absorption test results increase as the percentage of Bamboo Ash increases due to particle size and air void, but the compressive strength decreases at 28 days.